Insider Bargaining Power, Starting Wages, and Involuntary Unemployment - Nils Gottfries; Tomas Sjöström (Uppsala University, Department of Economics, 1999)
Recent analyses of wage bargaining has emphasized the distinction between insiders and outsiders, yet one typically assumes that insiders and recently hired outsiders are paid the same wage. We consider a model where the starting wage for outsiders may be lower than the insider wage, but incentive constraints associated with turnover affect the form of the contract. We examine under what conditions the starting wage is linked to the insider wage so that increased bargaining power of insiders raises the starting wage and reduces hiring of outsiders.
Keywords: J23; J31; J33; 330; starting wage; bargain; seniority; unemployment